(untitled) (Global Journal of Human-Social Science, 2014)
This article discusses the past twenty-five years of economic and political transition in Poland. It traces the origin of the "Polish dilemma" by pointing out the "Grand Failures" of the command-and-control economy; discusses the philosophical underpinnings of the reform effort; and delineates the major components of the Balcerowicz Plan-with a special emphasis on Poland’s privatization program. The article then moves to a discussion of the importance of Foreign Direct Investment (FDI) in the Polish economy and describes several important surveys which point to the success of the Polish experiment in areas such as business attractiveness, overall climate for business, and business friendliness. In addition to providing up-to-date statistics on Polish economic performance through the end of 2013, the article concludes with an observation as to the future for Poland’s commitment to economic change and economic development.